A Pilot Feasibility Study of an Undergraduate Nursing Student Harm Reduction Community Health Placement - Woo, Miriam; Ferreira, Carla; Ens, Twyla; Ginn, Carla; Jackson, Jennifer (Quality Advancement in Nursing Education / Avancées en formation infirmière, 2025)
Background: Nursing students may struggle with community placements, preferring hospital placements because of the emphasis on acute care. There are limited numbers of community health nurses available for students, so settings outside of health services can be used as venues for community health placements.Purpose: We aimed to evaluate a pilot placement outside of health services setting in the context of a research study focused on harm reduction for people who use substances, to assess whether the placement was effective in engaging students with the full scope of community health nursing (CHN).Methods: We evaluated students’ experiences in this clinical placement using a thematic analysis approach to semi-structured qualitative interviews. We recruited students after their placements were completed and their final grades were submitted.Results: Three students participated in this evaluation and reported an increased understanding of CHN principles, such as social justice and equity, to address how social determinants of health affect clients. They also gained insight into the value of evidence-based practice and the full scope of CHN, particularly how it intersects with harm reduction. The nursing instructor role was critical to the success of the placement. Students wanted to have a higher level of interaction with people facing structural barriers to health during the placement.Conclusion: Our placement outside of health services settings was effective in expanding nursing students’ understanding of the full scope of CHN practice, including social determinants of health. Future studies can expand on this pilot to assess the value of diverse community placements for students.